Designing Animated Pedagogical Agent (APA) To Scaffold Student Learning In Online Problem-Based Learning (PBL) Environment - Shahbodin, F.; Abd Talib, Rosfatimah (MTUN UTeM, 2012)
This paper describes on the idea in integrating APA as an alternative approach as scaffolding in PBL. APA will be operated as a virtual tutor and guide learners through the learning process in PBL environment.